Effects of ankle dorsiflexion training on the medial longitudinal arch of the foot - Oyama, Shimpei; Shinohara, Hiroshi (International journal of exercise science, 2020)
[Purpose] The height of the medial longitudinal arch at rest and the height of the tibialis anterior muscle train were measured in healthy subjects in sitting and standing positions, and how the anterior tibial muscle affected the arch height The purpose was to verify whether or not to give. [Subjects and Methods] The arch height was measured for 20 legs of 10 female students using an ultrasonic diagnostic imaging system. The arch height ratio was compared before and after performing the ankle dorsiflexion exercise using a tube. [Results] No significant difference was observed in any case. [Conclusion]In this study, the arch did not change after training. However, if the arch was considered to be low, it was suggested that the dorsiflexion of the ankle may increase the height of the medial vertical arch.